2001
DOI: 10.1007/s00464-001-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for inflammatory bowel disease

Abstract: Although STC is a far more extensive procedure than ICR, the overall postoperative complication rate is not significantly different between the two groups; however, we found that there were more intraoperative complications associated with STC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
(27 reference statements)
3
25
1
2
Order By: Relevance
“…[26][27][28] Nevertheless, the nature of complicated CD can render surgery challenging and the technical difficulties encountered are more pronounced with laparoscopic surgery. [29][30][31][32] Penetrating CD (i.e. intraabdominal abscess and fistula) was an independent factor predicting conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Nevertheless, the nature of complicated CD can render surgery challenging and the technical difficulties encountered are more pronounced with laparoscopic surgery. [29][30][31][32] Penetrating CD (i.e. intraabdominal abscess and fistula) was an independent factor predicting conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Could these patients be at a higher risk of developing postoperative pneumoperitoneum? No study answers this question directly; however, it has been shown that patients with inflammatory bowel disease are at a higher risk of postoperative complications [15,16] . One of the possible complications is anastomotic leaks, which in turn, has been shown to be a cause of postoperative pneumoperitoneum [1,15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…No study answers this question directly; however, it has been shown that patients with inflammatory bowel disease are at a higher risk of postoperative complications [15,16] . One of the possible complications is anastomotic leaks, which in turn, has been shown to be a cause of postoperative pneumoperitoneum [1,15,16] . These patients are at a higher risk for leaks due to their immunosuppressed state and overall inflammatory disease process causing tissue friability and dense adhesions [16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations